Audrey, wait! - Benway, Robin (New York : Razorbill, 2008)
Audrey Cuttler's life is turned upside down when her ex-boyfriend's song about their break up hits the top of the charts, making Audrey a prime target for the paparazzi, who are documenting her every move, hoping to catch her messing up, and causing her nothing but misery.
Young Adult
Young Adult
School Library Journal
Bulletin of the Center for Children's Books starre
Pub Weekly
Keywords: Dating (Social customs) -- Juvenile fiction; Fame -- Juvenile fiction; Dating (Social customs) -- Fiction; Fame -- Fiction; Dating (Social customs) -- Fiction; Fame -- Fiction